2004
DOI: 10.2466/pms.99.3f.1231-1238
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Power of Basketball Game-Related Statistics by Level of Competition and Sex

Abstract: The purpose of this study was to identify the basketball game-related statistics that best discriminate performances by sex of players and level of competition. Archival data were obtained from the International Basketball Federation boxscores for all games during men's senior (n=62), men's junior (n=64), women's senior (n=62), and women's junior (n=42) World Championships. The game-related statistics gathered included 2- and 3-point field-goals (both successful and unsuccessful), free-throws (both successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 7 publications
(8 reference statements)
4
45
1
5
Order By: Relevance
“…World Basketball Championships have also been studied in different categories. In World Junior Basketball Championship (Ibáñez, Sáenz-López, Giménez, Sampaio, & Janeira, 2003) and comparision between junior and senior (García, Ibáñez, Parejo, Cañadas, & Feu, 2010;Sampaio, Ibáñez, & Feu, 2004). The results of these investigations perfectly describe each competition.…”
Section: Introductionsupporting
confidence: 68%
“…World Basketball Championships have also been studied in different categories. In World Junior Basketball Championship (Ibáñez, Sáenz-López, Giménez, Sampaio, & Janeira, 2003) and comparision between junior and senior (García, Ibáñez, Parejo, Cañadas, & Feu, 2010;Sampaio, Ibáñez, & Feu, 2004). The results of these investigations perfectly describe each competition.…”
Section: Introductionsupporting
confidence: 68%
“…However, although international competitions are held not only for men, but also for women, previous studies on regional differences in basketball [2,3] have analyzed only men’s competitions. Sex differences in performance profiles have been reported in previous studies [4,5,6]. For example, Sampaio et al [4] analyzed the world championships for both men and women held in 2002 and reported that men’s teams were discriminated from women’s teams by a higher percentage of blocks and a lower percentage of steals, suggesting that anthropometric differences between men and women might be attributable to the difference in performance profiles.…”
Section: Introductionmentioning
confidence: 90%
“…In fact, the average height of the players in the top eight teams of egy and tactics which would be reflected in game-related statistics. However, studies on game-related statistics of women's basketball are limited (7)(8)(9), and to the author's knowledge, no studies on those of Asian women's basketball have been published in major English-language journals in the field of sports science. Therefore, the purpose of this study was to investigate whether game-related statistics which discriminate winners from losers in women's basketball differ between Asian and European competitions.…”
Section: Introductionmentioning
confidence: 99%